Increased 5-HT(2A) receptor binding in euthymic, medication-free patients recovered from depression: a positron emission study with [(11)C]MDL 100,907. - Bhagwagar, Z; Hinz, R; Taylor, M; Fancy, S; Cowen, P; Grasby, P (2006)
OBJECTIVE: A previous positron emission tomography (PET) study reported increased serotonin 5-HT(2A) receptor binding in unmedicated depressed patients with high scores on the Dysfunctional Attitudes Scale. The purpose of the present study was to use the highly selective 5-HT(2A) receptor ligand [(11)C]MDL 100,907 in a PET imaging paradigm to assess 1) 5-HT(2A) receptor binding potential in euthymic subjects with a history of recurrent depression and 2) the relationship between receptor binding and scores on the Dysfunctional Attitudes Scale. METHOD: Cortical 5-HT(2A) receptor binding was measured in 20 unmedicated, fully recovered unipolar depressed patients and 20 age- and gender-matched comparison subjects. Regional estimates of binding potential were obtained using a reversible plasma input function compartmental model and the cerebellum as a reference region to estimate the free and non-specifically bound [(11)C]MDL 100,907 in brain tissue. RESULTS: Relative to the comparison subjects, the recovered depressed patients demonstrated significantly higher 5-HT(2A) receptor binding potential in the frontal cortex (mean increase: 19%), parietal cortex (mean increase: 25%), and occipital cortex (mean increase: 19%). 5-HT(2A) receptor binding potential correlated negatively with age in both patients and comparison subjects and positively with the Dysfunctional Attitudes Scale in the recovered patients. CONCLUSIONS: These findings should be considered preliminary but suggest that recovered subjects with a history of recurrent major depression have elevated binding potential of cortical 5-HT(2A) receptors. The correlation of increased 5-HT(2A) receptor binding potential with increased scores on Dysfunctional Attitudes Scale supports earlier work suggesting that increased 5-HT(2A) receptor availability characterizes a group of depressed patients with high levels of dysfunctional attitudes.